Von Neumann-Morgenstern farsightedly stable sets in two-sided matching - Vincent J. Vannetelbosch; Ana Mauleon; Wouter Vergote (Theoretical Economics, 2011)
We adopt the notion of von Neumann-Morgenstern (vNM) farsightedly stable sets to determine which matchings are possibly stable when agents are farsighted in one-to-one matching problems. We provide the characterization of vNM farsightedly stable sets: a set of matchings is a vNM farsightedly stable set if and only if it is a singleton subset of the core. Thus, contrary to the vNM (myopically) stable sets [Ehlers, J. of Econ. Theory 134 (2007), 537-547], vNM farsightedly stable sets cannot include matchings that are not in the core. Moreover, we show that our main result is robust to many-to-one matching problems with substitutable preferences: a set of matchings is a vNM farsightedly stable set if and only if it is a singleton set and its element is in the strong core.
Keywords: C70; C78; 330; Matching problem; von Neumann-Morgenstern stable sets; farsighted stability